I Want You! The Evolution of the All-Volunteer Force - Rostker, Bernard D. (RAND Corporation, 2006)
As U.S. military forces appear overcommitted and some ponder a possible return to the draft, the timing is ideal for a review of how the American military transformed itself over the past five decades, from a poorly disciplined force of conscripts and draft-motivated "volunteers" to a force of professionals revered throughout the world. Starting in the early 1960s, this account runs through the current war in Iraq, with alternating chapters on the history of the all-volunteer force and the analytic background that supported decisionmaking. The author participated as an analyst and government policymaker in many of the events covered in this book. His insider status and access offer a behind-the-scenes look at decisionmaking within the Pentagon and White House. The book includes a foreword by former Secretary of Defense Melvin R. Laird. The accompanying DVD contains more than 1,700 primary-source documents-government memoranda, Presidential memos and letters, staff papers, and reports-linked directly from citations in the electronic version of the book. This unique technology presents a treasure trove of materials for specialists, researchers, and students of military history, public administration, and government affairs to draw upon.